All hail? The impact of ride hailing platforms on the use of other transport modes - Ciarán Mac Domhnaill (University College Dublin, UCD School of Economics, 2024)
Does ride hailing complement or substitute other forms of transport, such as public transport? I employ Scottish Household Survey travel diary data from 16,712 individuals between 2012 and 2019 in a difference-in-differences examination of how ride hailing affected the use of other transport modes. Results reveal a small complementary effect on the use of public transport relative to driving a car in Glasgow, although this is not reflected in Edinburgh. The Glasgow effect appears to be more pronounced among individuals who are younger, male, employed and with higher levels of household income
Keywords: R41; R40; H42; O33; 330; ride hailing; public transport; technological innovation; sharing economy; difference-in-differences; travel diary